Implementation of Student Field Practice Program (Internship) PGMI Study Program at SD/MI Palangka Raya City: Pelaksanaan Program Praktek Lapangan Mahasiswa (Magang) Prodi PGMI SD/MI Kota Palangka Raya - Sulistyowati, Sulistyowati; Mahmudah, Istiyati; Norliana, Norliana (Universitas Muhammadiyah Sidoarjo, 2023)
As an effort to improve the quality of education, the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) IAIN Palangka Raya implements a field practice program or apprenticeship which is divided into 3 stages, namely apprentice 1, apprentice 2, and apprentice 3. The field practice program is one of the courses that must be completed by students with the aim of preparing professional student human resources. This study aims to explain the planning, implementation, and evaluation of the field practice program (internship) for PGMI study program students at SD/MI in Palangka Raya City. The method in this study is a qualitative method with a descriptive approach, with data collection techniques through interviews, observation, and documentation. The research was conducted in 5 schools in SD/MI Palangka Raya City. The results of this study are planning a field practice program carried out by forming an apprenticeship committee, searching for, visiting, assigning, holding meetings between lecturers and apprentice agencies, preparing applications for internship placements and sending them to schools, grouping apprentices along with supervisors, handing over student apprentices, preparation of apprenticeship programs, as well as orientation and observation in schools under the guidance of tutors. As for the implementation of apprentice 1, namely observing school administration, apprentice 2 being an observer and assistant teacher, and apprentice 3 teaching practicum directly. The evaluation of apprenticeship activities is the merging of apprentice 1 to apprentice 2.